2022
DOI: 10.1155/2022/7728975
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Merozoite Surface Protein-1 and -2 Genes in Plasmodium falciparum Isolates among Asymptomatic Population in Boset and Badewacho Districts, Southern Ethiopia

Abstract: Background. The genetic variation of Plasmodium falciparum has been studied to assess local malaria transmission genetic profile using evidence-based intervention measures. However, there are no known previous reports of P. falciparum polymorphism in Badewacho and Boset districts, Southern Ethiopia. The purpose of this study was to determine the genetic diversity of the merozoite surface protein-1 and -2 (msp-1 and msp-2) allelic families in P. falciparum isolates from an asymptomatic populations. Methods. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…However, these one outlier individual studies were not included in the meta-analysis. This study showed that, the pooled prevalence of msp-1 gene was 100% (surrounding Adama) (35). Moreover, the overall prevalence of P. falciparum with msp-1 gene is high (84%), even though some of the individual studies have not detected the msp-1 gene.…”
Section: Sensitivity Analysismentioning
confidence: 71%
“…However, these one outlier individual studies were not included in the meta-analysis. This study showed that, the pooled prevalence of msp-1 gene was 100% (surrounding Adama) (35). Moreover, the overall prevalence of P. falciparum with msp-1 gene is high (84%), even though some of the individual studies have not detected the msp-1 gene.…”
Section: Sensitivity Analysismentioning
confidence: 71%
“…Genetic diversity of P. falciparum is a critical factor in uencing the epidemiology, transmission dynamics and potential for the development of antimalarial drug resistance. Merozoite surface proteins (MSPs), such as MSP1 and MSP2, have been extensively studied as genetic markers to assess the diversity and complexity of P. falciparum infections [13][14][15]. Knowledge of the genetic characteristics of malaria parasites is essential for tailoring control strategies.…”
Section: Introductionmentioning
confidence: 99%